جامعہ فتح العلوم، شیوہ (صوابی)کی اصلاحی و سماجی خدمات کا تحقیقی جائزہ: A Research Study of Reformative and Social Services of Jamia Fathul Uloom Shewa (Swabi) (Al-Aasar, 2025)
Jamia Fath-ul-Uloom, Shewa (Swabi) stands as a prominent reformative institution, contributing significantly to the development of society through its academic, intellectual, missionary and social services. The institution operates under a comprehensive and systematic framework focused on the correction of beliefs (Aqeedah), proper observance of worship, and enhancement of moral and ethical values. With a harmonious integration of teaching and preaching, the Jamia provides structured religious education to the younger generation while actively working toward eradicating social evils. Its reformative initiatives go beyond academic boundaries, fostering intellectual awakening, religious awareness, and communal harmony among the general public. Jamia Fath-ul-Uloom is a radiant beacon of knowledge and reform—a guiding light rooted in a glorious past, a vibrant present, and a promising future. Its impactful efforts have brought meaningful change to the lives of youth, women, and the general populace across the region of Swabi, laying a strong foundation for a better religious and worldly life.